Estimation of the Temporal Structure of Interest Rates in Chile, 1994-1997 - Zúñiga, Sergio; Soria, Karla (Estudios de Administración, 1999)
In this paper we empirically estimate the structure of the interest rates in Chile by using Nelson and Siegel 1987 parsimonious nonlinear specification. We work with daily yields from discount bonds of the Chilean government, which are traded at the Bolsa de Comercio de Santiago (Santiago Stock Exchange) during 1994-1997. Since the transactions of the instruments are unable to satisfactorily fill the spectrum of terms to maturity, the information is added, which implies performing monthly average estimates of the term structure for the 1994:01-1997:12 period. In agreement with the evidence from previous studies, the results in every month invariably confirmed descending spot curves with regard to the time to maturity, while forward curves always were below spot curves. According to the pure expectations theory, it is probable that much of this effect be due to the fact that current levels of the rates were above their steady state levels. Like other theories, the one on segmented markets also offers a commendable explanation for the persistent negativity of the term structure of interest rates.